Chemicaland physical atributes of a latosoland coffee crop nutrition in agroforestry and conventional management systems - Carmo, Davi Lopes; Nannetti, Dulcimara Carvalho; Dias Junior, Moacir Souza; Lacerda, Tales Machado; Nannetti, Alex Nogueira; Manuel, Lourenço (Coffee Science - ISSN 1984-3909, 2014)
In search of a sustainable coffee sector production, various management practices have been adopted, because it causes changes in the physical and chemical soil attributes, consequently changes the coffee crop nutrition. The aim of this study was to evaluate soil quality by quantifying the physical and chemical attributes of a Red Latosol and the nutritional status of the coffee culture in two management systems: conventional and agroforestry in southern Minas Gerais, Brazil. The study was conducted in the municipality of Machado - MG in 2008. Samples deformed and non-deformed soil were collected for chemical and physical analyses. The chemical analyses evaluated were: contents of P, K+, Ca2+, Mg2+, H++Al3+, Al3+, CTC, V, MOS and m. The physical attributes analyzed were Ds, VTP, Ma, Mi and Ma/Mi. Leaves were collected to analyze the contents of N, P, K, Ca, Mg and S. The chemical attributes of the soil in the agroforestry system seemed to be more favorable to the coffee culture, in comparison to the conventional system. The physical attributes did not changed between the management systems. Coffee plants cultivated in agroforestry system promoted positive nutrient cycling, as well as, the macronutrients contents increased in the leaf tissue reaching similar levels of the coffee plantation in conventional system.